PENGARUH MEDIA KOMIK TERHADAP MINAT BACA SISWA KELAS II SDN 1 TELUK KIJING - Siska Novitasari; Linda Lia; Tanzimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using comic media on the reading interest of second-grade elementary school students. This research uses a quantitative approach with an experimental method of the True Experimental Design type, using a Posttest Only Control Design. The sample in this study consisted of two classes, namely class II.A as the experimental class and class II.B as the control class, with a total of 31 students at SDN I Teluk Kijing. Data were collected through questionnaires and interviews. The results showed that the average reading interest score in the experimental class was 76.47, while the control class scored 70.10. Data were analyzed using the Independent Sample T-test, resulting in a t-value (tcount) of 2.583 and a t-table value (ttable) of 0.3550 at a significance level of 0.05. Since tcount > ttable, the alternative hypothesis (Hₐ) is accepted. Therefore, it can be concluded that the use of comic media has an effect on the reading interest of second-grade elementary school students.